Keterkaitan Konsumsi Energi Rumah Tangga dengan Karakteristik Perilaku Masyarakat di Kota Tegal - Aida Ulfa Faza; Jawoto Sih Setyono (Jurusan Perencanaan Wilayah dan Kota, 2018)
The development of urban space can be seen from how space was used and some characteristics of community behaviour. One of the factors influences the development of space is urbanization. One of the impacts of urbanization is an increase in energy consumption which is also reflected in Central Java Province with moderate to high urbanization levels, experienced an increase in energy consumption from 2011-2014. Tegal City experienced the urbanization as reflected by some characteristics of society behaviour such as modern lifestyle, land use, and socio-economic characteristics which is enable to increasing energy consumption. The limited of energy source followed by high energy consumption, attracting much attention to seek the fulfilment of energy needs. The purpose of this research is to know the relationship of household energy consumption between characteristics of community behaviour in Tegal City. In this study, the characteristics of community behaviour are assessed from several variables such as community behaviour related to urbanization, land use, travel behaviour and socio-economic aspects. While energy consumption is defined as the unit of BTU (British Thermal Unit) for every need of electricity and fuel (gasoline) supporting the movement of members in the household. The analysis used is multiple linear regression analysis with characteristics of community behaviour as independent variable and energy consumption as the dependent variable. The results showed that the consumption of electrical energy is influenced by the intensity of the use of washing machines and the intensity of the use of air conditioning. Both variables are variables of urbanization aspect. While the consumption of fuel energy (gasoline) is influenced by the number of motorized travel which is a variable of the aspects of travel behaviour and is influenced by the number of private motor vehicles that are variables of socio-economic aspects.